Cost-benefit of the telecardiology service in the state of Minas Gerais: Minas Telecardio Project - Andrade, Mônica Viegas; Maia, Ana Carolina; Cardoso, Clareci Silva; Alkmim, Maria Beatriz; Ribeiro, Antônio Luiz Pinho (Arquivos brasileiros de cardiologia, 2011)
Telecardiology is a tool that can aid in cardiovascular care, mainly in towns located in remote areas. However, economic assessments on this subject are scarce and have yielded controversial results. To evaluate the cost-benefit of implementing a Telecardiology service in remote, small towns in the state of Minas Gerais, Brazil. The study used the database from the Minas Telecardio (MTC) Project, developed from June 2006 to November 2008, in 82 towns in the countryside of the state. Each municipality received a microcomputer with a digital electrocardiograph, with the possibility of transmitting ECG tracings and communicating with the on-duty cardiologist at the University hospital. The cost-benefit analysis was carried out by comparing the cost of performing an ECG in the project versus the cost of performing it by patient referral to another city. The average cost of an ECG in the MTC project was R$ 28.92, decomposed into R$ 8.08 for the cost of implementation and R$ 20.84 for maintenance. The cost simulation of the ECG with referral ranged from R$ 30.91 to R$ 54.58, with the cost-benefit ratio being always favorable to the MTC program, regardless of the type of calculation used for referral distance. The simulations considered the financial sponsor's and society's points-of-view. The sensitivity analysis with variation of calibration parameters confirmed these results. The implementation of a Telecardiology system as support to primary care in small Brazilian towns is feasible and economically beneficial, and can be used as a regular program within the Brazilian public health system.